Enhancing Learning Quality in Elementary School Using a Scientific Approach and Quantum Teaching - Mutiara Putri, Sheryl; Sanusi, Anwar; Marini, Arita; Zakiah, Linda (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This research aims to improve learning quality by implementing a scientific approach with quantum teaching settings in elementary school. The research method used is classroom action research, which has two cycles. Data collection instruments include observation sheets for implementing scientific approaches with quantum teaching settings and test items for learning outcomes. The results of the study show that in cycle I, both the teacher's skills and student activities indicate that students enjoy the learning activities, as evidenced by the emoticon choices of the 24 attending students; eight students chose the